The relative contribution of genetic and environmental factors to cancer risk and cancer mortality in Norway - Edwin Leuven; Erik Plug; Marte Rønning (University of Oslo, Department of Economics, 2014)
Using Norwegian cancer registry data we study twin and non-twin siblings to decompose variation in cancer at most common sites and cancer mortality into a genetic, shared environment and individual (unshared environmental) component. Regardless the source of sibling variation, our findings indicate that genes dominate over shared environment in explaining relatively more of the variation in cancer at most common cancer sites (but lung and skin cancer) and cancer mortality. The vast majority of the variation in cancer and cancer mortality, however, is explained by individual (unshared environmental) factors.
Keywords: I12; J62; 330; Cancer; Twins; Heritability; Environment